Effect of InxAl1-xAs graded buffer materials on pseudomorphic InP HEMT - Ai, Likun; Tian, Fangkun; Xu, Anhuai; Huang, Hua; Qi, Ming (Frontiers in Materials, 2022)
In this paper, The InxAl1-xAs graded buffer was inserted between the InAlAs buffer layer and the pseudomorphic In0.66Ga0.34As channel layer to improve material quality in channel. The results show that the InxAl1-xAs graded buffer layer with 50nm thickness can obtain a good heterojunction interface and the root mean square (RMS) of 0.154nm. The two dimensional electron gas (2-deg) mobility and concentration were 8570cm2/Vs and 2.7×1012cm-2 at 300K, respectively. InxAl1-xAs graded buffer layer can enhance the interface quality and the electrical performance through releasing the interface strain caused by pseudomorphic In0.52Al0.48As/In0.66Ga0.34As HEMT. This study shows great potentials by incorporating InxAl1-xAs graded buffer layer in pseudomorphic InP HEMT materials to improve the properties of devices.